1980
DOI: 10.1159/000455539
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Plasma Renin in Developing Piglets

Abstract: Plasma renin activity (PRA) was determined in conscious piglets between 1 and 50 days of age before and after treatment with saralasin and indornethacin. Following drug treatment, animals were volume expanded with isotonic saline. Saralasin increased PRA in piglets 1--5 and 18-22 days of age but not 45-50 days. Neither indome thacin nor VE changed PRA at any age, Volume expansion of saralasin- and indomethacin-treated pigs decreased PRA. Neonatal hyperrenincmia does not appear to result from renin release stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…As described previously [52], in the control period, the piglet PRA of 1.49 + 0.35 ng angiotensin I/ml per hour was significantly greater than the adult PRA (0.36 + 0.15 ng angiotensin I/ml per hour). Intrarenal infusion of L-NAME did not significantly change PRA in the adult pig from control levels.…”
Section: No and Renin Release In The Developing Kidneysupporting
confidence: 73%
“…As described previously [52], in the control period, the piglet PRA of 1.49 + 0.35 ng angiotensin I/ml per hour was significantly greater than the adult PRA (0.36 + 0.15 ng angiotensin I/ml per hour). Intrarenal infusion of L-NAME did not significantly change PRA in the adult pig from control levels.…”
Section: No and Renin Release In The Developing Kidneysupporting
confidence: 73%
“…Despite reports by Thompson and Weiner that indicate adaptations in the sensitivity of vascular smooth muscle to NO increases after birth (24), renal blood flow remains low in the newborn due to the enhanced vasoconstrictor response of the RAS (8-11). To counter-balance the elevated RAS of the newborn and to maintain adequate RBF and GFR, studies have demonstrated a crucial enhanced role of NO in the neonate's renal hemodynamic state.…”
Section: Discussionmentioning
confidence: 91%
“…Studies involving various species have suggested RVR is further enhanced in the afferent arterioles of the newborn kidney causing functional decreases in RBF, GFR, and filtration fraction, thus highlighting the hemodynamic significance of enhanced vascular resistance in the newborn's afferent arterioles (1,6,7). The major vasoactive agent that causes the newborn's elevated RVR is the renin-angiotensin system (RAS) (8-11). Many components of the RAS are developmentally regulated in the immature preglomerular resistance vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated the primary vasoactive factor that effects neonate RVR is the renin-angiotensin system (RAS) [17,[21][22][23][24][25][26][27]. The major components of the RAS, including renin, angiotensin II (ATII), and both ATII receptor subtypes (AT1 and AT2), are highly present in the immature kidney, but their anatomical distribution and activities are quite different than those seen in the adult kidney [21,[28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%